How does the pattern of root metabolites regulating beneficial microorganisms change with different grazing pressures? - Yuan, Ting; Ren, Weibo; Wang, Zhaoming; Fry, Ellen L.; Tang, Shiming; Yin, Jingjing; Zhang, Jiatao; Jia, Zhenyu (Frontiers in Plant Science, 2023)
Grazing disturbance can change the structure of plant rhizosphere microbial communities and thereby alter the feedback to promote plant growth or induce plant defenses. However, little is known about how such changes occur and vary under different grazing pressures or the roles of root metabolites in altering the composition of rhizosphere microbial communities. In this study, the effects of different grazing pressures on the composition of microbial communities were investigated, and the mechanisms by which different grazing pressures changed rhizosphere microbiomes were explored with metabolomics. Grazing changed composition, functions, and co-expression networks of microbial communities. Under light grazing (LG), some saprophytic fungi, such as Lentinus sp., Ramichloridium sp., Ascobolus sp. and Hyphoderma sp., were significantly enriched, whereas under heavy grazing (HG), potentially beneficial rhizobacteria, such as Stenotrophomonas sp., Microbacterium sp., and Lysobacter sp., were significantly enriched. The beneficial mycorrhizal fungus Schizothecium sp. was significantly enriched in both LG and HG. Moreover, all enriched beneficial microorganisms were positively correlated with root metabolites, including amino acids (AAs), short-chain organic acids (SCOAs), and alkaloids. This suggests that these significantly enriched rhizosphere microbial changes may be caused by these differential root metabolites. Under LG, it is inferred that root metabolites, especially AAs such as L-Histidine, may regulate specific saprophytic fungi to participate in material transformations and the energy cycle and promote plant growth. Furthermore, to help alleviate the stress of HG and improve plant defenses, it is inferred that the root system actively regulates the synthesis of these root metabolites such as AAs, SCOAs, and alkaloids under grazing interference, and then secretes them to promote the growth of some specific plant growth-promoting rhizobacteria and fungi. To summarize, grasses can regulate beneficial microorganisms by changing root metabolites composition, and the response strategies vary under different grazing pressure in typical grassland ecosystems.